تقسيم العالم بين الأصول الإسلامية والتنظيم الدولي المعاصر - بوقرة, سفيان (University of Eloued جامعة الوادي, 2021)
تقسيم العالم أو كما يسمى المعمورة ويقصد به الأرض، إلى إقليمين أو أكثر سواء من النظرة الفقهية الإسلامية، أو الرؤية الغربية الحديثة، ما هو إلا اصطلاح واجتهاد بشري، يريد كل طرف تبرير هذا الطرح، باعتباره وسيلة من الوسائل للتنظيم الدولي والعالمي، ففي الوقت الذي نجد فيه أصحاب النظرة الفقهية الإسلامية يوردون أن تقسيمهم للعالم جاء من أجل نشر الدعوة والخير للعالم وحماية لبيضة الإسلام ودولته، يظهر جليا أنّ التقسيم الحديث للعالم من طرف بعض الدول لم يزد إلاّ من توسع الفجوة وتكبير الشرخ الحاصل بين مجموعة الدول الغنية والفقيرة، وفقر هذه الأخيرة كان نتيجة استعمار واحتلال واستغلال الأولى لها، فشتان بين تقسيم جاء للحماية والعدل، وآخر جاء للاستعمار والتفقير والتجهيل. The world, as it called the globe or the earth, is devided into two regions or more either from the Islamic jurisprudential view or the modern Western vision.This division is just a human term and endeavor through which each party wants to justify its proposal as a means of international and global organization. At a time when we find the holders or owners of Islamic jurisprudence view stating that their division of the world came to spread the Islamic call, goodness to the world and to unify the Islamic countries, it is clearly showed that the modern division of the world by some countries has only increased and widened the gap between the rich and poor countries, and that the poverty of the latter was the result of colonialism, occupation and exploitation of the former .There is a big difference between a division that came for protection and justice and another for colonialism, poverty and ignorance.
مجلد12، عدد1
Keywords: الحرب ; السلم ; المنظمات الدولية; War ; peace ; International Organizations